The neuropsychology of visual feature binding - Humphreys, G; Jane Riddoch, M (Elsevier, 2005)
This chapter reviews evidence from the neuropsychology of feature binding that reveals that (a) binding processes are mediated by the parietal lobe and (b) several binding processes may take place at different stages of vision. The relations between neuropsychological disorders of binding and synesthesia are discussed. Although both the temporal and spatial binding accounts stress the operation of a single binding process, there is some suggestion that several forms of binding operate, probably modulated by different brain regions. © 2005 Elsevier Inc. All rights reserved.